European Medicines Agency Initiatives for Acceleration of Development Support and Evaluation Procedures for COVID-19 Treatments and Vaccines - de Farmacoterapia, Revista Portuguesa (2020)
The European Medicines Agency published in May 2020 the document «EMA initiatives for acceleration of development support and evaluation procedures for COVID-19 treatments and vaccines». Below, a summary of the document is presented with aspects that we consider particularly relevant. Available in: https://www.ema.europa.eu/en/documents/other/ema-initiatives-acceleration-development-support-evaluation-procedures-covid-19-treatments-vaccines_en.pdf.